Risks and opportunities of reshaping global value chains - Crowe, David (OECD Publishing, 2023)
The paper reviews selected implications of trade integration via global value chains (GVC) and identifies gaps in understanding of GVC risks. Despite recent significant progress, many GVC risks remain unknown. The paper also discusses pros and cons of possible strategies to minimise GVC risks and specific measures that are debated in the literature. None of the proposed strategies is a silver bullet and best measures are likely to vary across products and sectors. Most actions to improve resilience lie with firms rather than governments. There is less controversy about governments taking a more proactive role in co-ordinating data collection, analysing GVC risks and collaborating with private firms to promote standards of conduct. In contrast, there is less agreement about governments using financial incentives, regulatory requirements and direct government control to reshape GVCs. Government intervention risks creating costly distortions without minimising economic volatility and improving national security, and making international co-operation regarding social and environmental goals more difficult
Keywords: Economics